CHALLENGES OF INTERPRETING THE NOTION OF SOFTWARE COPYRIGHTS IN THE CURRENT ECONOMIC AND SOCIO-POLITICAL CONTEXT - Ramona DUMITRAȘCU (Challenges of the Knowledge Society)
Every country has it’ s own interpretation and enforcement of copyrights. The challenge is in case of a conflict of interpretations to create a common structure accepted by all parties as a base of mutual understanding and agreement. ESCIA guidelines seek to provide a scalable assessment framework which in turn can be a tool for research and development of structures to deal with the different cultural and social economic circumstances of the different countries / the assessment of which system is dominant is an ongoing, ever-changing debate for which you need the guideline tools to steer the discussion in the right direction which is a challenge on it’s own.the digital economy is the most important part of the global economy.The digital transformation of international production requires regulation,governing, investor behaviour. The negative impact of manipulation of data obtained from consumers by global powerfull multinationals is to be considered a major insentive for a rigourus monitorization and regulation of international productions. The diversity of interests, political and finacial, make fair regulations covering all aspects of the situation, extremlely difficult, in addition to the ever chainging parameters governing the subject as such. The complexity of the matter should not prevent an indepth assassement and solution seeking policy.